Discovery of electronic information in legal proceedings in South Africa with specific reference to Rule 23 of the Magistrates’ Court Rules and Rule 35 of the Uniform Rules of Court - Gravett, Willem (University of Pretoria, 2023)
Dissertation (LLM)--University of Pretoria, 2022.